Bacteriological Characteristics of Wounds when Treating them with Newborn Piglets’ Skin Extract - Shkodovskaya, N. Yu.; Vysekantsev, I. P.; Galchenko, S. Ye; Sandomirsky, B. P. (Problems of Cryobiology and Cryomedicine, 2005)
Effect of placenta and newborn piglets’ skin extracts on bacteriological characteristic of burns and cold injures was studied in the work. The results obtained show that earlier eradication of wounds took place under injection of skin extract rather than under the one of placenta extract. Skin extract has more significant therapeutic action while treating burns and cold injures of the 2nd grade with purulent manifestation in comparison with placenta extract.